LOW LEVEL OF AFLATOXIN IN BROILER AT EXPERIMENTAL CONDITIONS. USE OF CELL WALL YEAST AS ADSORBENT OF AFLATOXIN - SANTIN, E.; PAULILLO, A.C.; KRABBE, E.L.; ALESSI, A.C.; POLVEIRO, W.J.C.; MAIORKA, A. (Archives of Veterinary Science, 2003)
Este estudo foi realizado para avaliar a eficácia da parede celular de Saccharomyces cerevisiae (PCSC) como inibidor dos efeitos tóxicos da aflatoxina em frangos de corte de 1 a 42 dias de idade. Foram utilizados 320 frangos distribuídos em quatro tratamentos com quatro repetições de 20 aves cada: T1- controle; T2 0.1% PCSC; T3 500 ppb de aflatoxina; T4 0.1% PCSC + 500 ppb de aflatoxina. Os parâmetros avaliados foram consumo de ração; ganho de peso; conversão alimentar; peso relativo de fígado, rins e bursa de Fabricius. O nível de Aflatoxina da dieta afetou (P<0,05) a conversão alimentar das aves aos 21 dias de idade, porém, não afetou (P>0,05) outros parâmetros de desempenho aos 21 e 42 dias de idade. A PCSC melhorou a conversão alimentar das aves expostas ou não à aflatoxina aos 42 dias de idade. A aflatoxina e/ou PCSC da dieta não afetaram o peso relativo dos órgãos avaliados. Não foram observadas interações entre aflatoxina e PCSC. Os resultados demonstram que, nos níveis utilizados no presente estudo, a aflatoxina não causa efeitos deletérios às aves em condições experimentais. Abstract This study aimed to evaluate the efficacy of cell wall of Saccharomyces cerevisiae (CWSC) as an inhibitor of the toxic effects of aflatoxin in broilers from 1 to 42 days of age. A total of 320 broilers were distributed in four treatments with four replicates of 20 birds each: T1- control; T2 0.1% CWSC; T3 500 ppb of aflatoxin; T4 0.1% CWSC + 500 ppb of aflatoxin. The parameters evaluated were feed intake; weight gain, feed conversion; relative weights of liver, kidneys and bursa of Fabricius. Although aflatoxin has decreased (P<0.05) the feed conversion of birds at 21 days of age, the levels provided did not affect (P>0.05) other performance parameters when the birds were at 21 and 42 days of age. The CWSC improved the feed conversion of birds exposed or not to aflatoxin at 42 days of age. The aflatoxin and / or CWSC in the diet did not affect the relative weight of evaluated organs. No interaction between CWSC and dietary aflatoxin was found. These results demonstrate that, at the levels given in this study, aflatoxin do not cause deleterious effects in the performance of broilers when in experimental conditions.